Factors influencing the implementation of good corporate governance in the public sector - Nirvana, Nirvana; Darmawati, Darmawati; Safitri, Ela (Social Sciences Insights Journal, 2025)
This study analyzes the factors influencing the implementation of Good Corporate Governance (GCG) in public sector organizations in Indonesia. GCG, which has its roots in private practice, is now crucial for Good Governance, improving resource efficiency, strengthening public accountability, and mitigating corruption. Although GCG has the potential to be transformative, its implementation faces unique bureaucratic complexities. This study uses a descriptive qualitative approach through an extensive literature review and regulatory analysis. We identify key internal factors: strong leadership commitment, adaptive organizational structure, effective internal control system, superior human resource quality, and optimal utilization of information/technology systems. External factors include a clear legal framework, the role of external oversight institutions, active community participation, and the influence of culture/social values. The results of this study are expected to provide an in-depth understanding of the challenges and opportunities for GCG adoption in the Indonesian public sector. It also presents practical implications for policymakers and practitioners in formulating adaptive and sustainable implementation strategies, for the sake of improving the quality of public services.